Flow-diverter reconstruction of an intracranial internal carotid artery dissection during thrombectomy for acute ischaemic stroke. Issue 1 (21st January 2020) - Gramegna, Laura Ludovica; Cardozo, Analía; Folleco, Edgar; Tomasello, Alejandro
Abstract : Intracranial carotid artery dissections are challenging, as there are no specific guidelines for their treatment, and most research suggests solutions for treating those involving extracranial vessels. We describe a patient with an acute ischaemic stroke within the territory of the right internal carotid artery, who was found to have intracranial carotid artery dissection during the thrombectomy procedure. The dissected lumen was successfully reconstructed via deployment of a Derivo flow-diverter stent. A balloon-assisted 'jacking' manoeuvre, in which a balloon is partially inflated at the beginning of the dissection to serve as leverage, was used to overcome the challenge of navigating the microcatheter tip through the stenosis proximal to the dissection. This case demonstrates the feasibly and safety of stenting with a flow diverter in a patient with internal carotid artery dissection; however, further studies are needed to confirm this finding.